2015
DOI: 10.1177/0961203315580870
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative dose of hydroxychloroquine is associated with a decrease of resting heart rate in patients with systemic lupus erythematosus: a pilot study

Abstract: CD-HCQ higher than 365 g was associated with a significant decrease (11%) in RHR in non-active SLE patients, although a larger prospective study is required to allow more definitive conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…However, it was reported to cause QT prolongation and decrease the resting HR. 3,4) Although such proarrhythmic effects were rarely seen and occurred usually after chronic use, we could not definitely exclude such a link in our patient based on a few acute cardiac toxicity cases with low doses of HCQ use, and the association between the normalization of the heart rhythm and QTc and the HCQ withdrawal further demonstrated that. A literature review revealed a case of recent onset of complete atrioventricular block just two days after HCQ initiation to treat systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 79%
“…However, it was reported to cause QT prolongation and decrease the resting HR. 3,4) Although such proarrhythmic effects were rarely seen and occurred usually after chronic use, we could not definitely exclude such a link in our patient based on a few acute cardiac toxicity cases with low doses of HCQ use, and the association between the normalization of the heart rhythm and QTc and the HCQ withdrawal further demonstrated that. A literature review revealed a case of recent onset of complete atrioventricular block just two days after HCQ initiation to treat systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 79%
“…24,25 In absolute numbers, at doses of 5 mg/kg weight/day, the risk of retinal toxicity at 5, 10 and 20 years of use is 1%, 2% and 20%, respectively. 26 What is important to highlight, is that retinal toxicity primarily occurs with high-dose usage for prolonged periods. In a cohort of 123 patients with rheumatoid arthritis, It must be realised that hydroxychloroquine use is associated with reduction in heart rate and cardiomyopathy.…”
Section: Hydroxychloroquine -Retinal Safetymentioning
confidence: 99%
“…Animal studies in mice and guinea pigs have shown that hydroxychloroquine reduces heart rate by acting on the sino-atrial node and modulating the hyperpolarisation-activated current. 25 In a study involving 45 patients with lupus on long-term hydroxychloroquine therapy, 18 patients with cumulative hydroxychloroquine intake of >365 g had a significantly lower mean heart rate of 65 ± 7 beats/min as compared with 73 ± 6 beats/min in 24 patients with cumulative hydroxychloroquine intake <365 g. 26 A person taking 400 mg of hydroxychloroquine per day would need to take it for 913 days continuously to reach a cumulative dose of 365 g.…”
Section: Hydroxychloroquine -Retinal Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxychloroquine has been found to decrease the resting heart rate in a cumulative dose-dependent fashion. 47 Further, hydroxychloroquine has been known to increase digoxin levels, and the medications should not be used in combination. 1 Whether the decrease in resting heart rate is associated with harm or benefi t and whether the effect is signifi cant enough to be considered when implementing therapy remain unanswered and deserve further investigation, as does the primary use of hydroxychloroquine for benefi cial lipid and glucose reduction in patients who are otherwise healthy.…”
Section: Negative Chronotropic Effect?mentioning
confidence: 99%